The trick with separation of variables is to write the solution $U$ as a product $X(x)T(t)$, so that your equation becomes
$$ X T'-t X T-t x X' T + t X' T = 0$$
Now divide through by $t X T$ so that we completely separate the dependence on $x$ and $t$ from each other:
$$\frac{T'}{t T} - 1 = (x-1) \frac{X'}{X} $$
Note that the left-hand-side only depends on $t$, while the right-hand side only depends on $x$. Thus, they are both constant, so we can set each side equal to some constant, $-\lambda$:
$$\begin{align} \frac{T'}{t T} - 1 &= -\lambda \\ (x-1) \frac{X'}{X} &= -\lambda \\ \end{align} $$
You may now solve each equation separately. I imagine you have initial conditions that will determine each component $X$ and $T$, and will determine $\lambda$.
EDIT
You will now see why I chose $-\lambda$ rather than $\lambda$. The solution of the $t$ equation is straightforward:
$$T(t) = T_0 e^{-(\lambda - 1) t^2/2} $$
The solution to the $x$ equation can be seen by rearranging terms:
$$(x-1)X'(x) + \lambda X(x) = 0$$
which may be rewritten as
$$ [(x-1)^{\lambda} X(x)]' = 0 \implies X(x) = X_0 (x-1)^{-\lambda}$$
Combining these solutions, we get
$$U(x,t) = X(x)T(t) = X_0 T_0 (x-1)^{-\lambda} e^{-(\lambda - 1) t} = K (x-1)^{-\lambda} e^{-(\lambda - 1) t^2/2}$$
You now need to specify some sort of initial conditions to determine $K$ and $\lambda$.